Biochemically confirmed smoking cessation and gestational weight gain. Issue 2 (11th January 2019) - Rockhill, Karilynn M.; England, Lucinda J.; Tong, Van T.; Sharma, Andrea J.
Abstract: Background: Prenatal smoking cessation has substantial health benefits for mothers and offspring, but concerns about weight gain may be a barrier to quitting. We quantified gestational weight gain associated with biochemically confirmed smoking cessation. Methods: Data originated from a randomized controlled cessation trial: Smoking Cessation in Pregnancy project (1987‐1991). We calculated gestational weight gain using self‐reported prepregnancy weight and measured weight at 30‐34 weeks of gestation. We used linear regression to estimate adjusted mean differences in gain for quitters versus continuing smokers by the last trimester. The effects of quitting earlier (by 2nd trimester) versus later (by 3rd trimester) were calculated. We assessed the percentages who gained weight according to Institute of Medicine (IOM) recommendations within 2 weeks of a full‐term delivery. Results: At 30‐34 weeks, nulliparous and multiparous quitters gained an average of 3.0 pounds (95% CI 0.9‐5.1 pounds) (1.4 kg [0.4‐2.3 kg]) and 6.6 pounds (95% CI 4.3‐8.9 pounds) (3.0 kg [1.9‐4.0 kg]) more, respectively, than continuing smokers. Weight gain in early quitters did not differ significantly from that in late quitters. Quitters were more likely than continuing smokers to gain above current guidelines (60.3% vs 46.3%) and were less likely to gain below guidelines (11.5% vs 21.6%) ( P  = 0.002). Conclusions: Although quitters had modest additional weight gain by 30‐34 weeks compared to continuing smokers, a high proportion in both groups gained in excess of IOM recommendations. Both quitters and continuing smokers may need support to achieve optimal gestational weight gain.